khi đặt $(dfrac{2}{3})^x=t$ thì phương trình $3^{2x+2}-2.6^x-7.4^x=0$ trở thành a. $7t^{2}-2t-9=0$ b. $7t^{2}+2t-9=0$ c. $3t^{2}-2t-7=0$ d. $3t^{2}-2t+7=0$  Giải chi tiết (nếu giải ra đáp án khác 4 đáp án trên thì mình sẽ xem lại đề bài và đáp án)

khi đặt $(\dfrac{2}{3})^x=t$ thì phương trình $3^{2x+2}-2.6^x-7.4^x=0$ trở thành a. $7t^{2}-2t-9=0$ b. $7t^{2}+2t-9=0$ c. $3t^{2}-2t-7=0$ d. $3t^{2}-2t+7=0$  Giải chi tiết (nếu giải ra đáp án khác 4 đáp án trên thì mình sẽ xem lại đề bài và đáp án)
Đăng phản hồi